Penerapan Metode Problem Solving pada Perkuliahan Fisika Terapan Taruna Teknika Nautika - Lusiani (Lembaga Penelitian dan Pengabdian Masyarakat, Akademi Maritim Nusantara Cilacap, 2022)
The application of problem solving methods in applied physics lectures for nautical engineering cadets, this is studied because the descriptions obtained can later be relevant to the results and learning motivation towards the digital transformation era in the future, so that there is hope for the continuity of the mind set as well as the choice of using strategies and learning media that can be used. for the next study. The purpose of the following study is to describe the application of problem solving methods in applied physics lectures for nautical engineering cadets. The method used is a survey, literature review. The object of research is the cadets of the engineering study program, Nautical AMN Cilacap. Psychomotor aspects of learning outcomes obtained through the method of discussion, observation. The study instrument is the google classroom media. According to the display in each picture, the problem solving stage is described in the applied physics course in nautical engineering. Stages 1 to 4 are described in Figures 1 to 10. The Engineering class is shown in Figures 1, 4, 5, 7, 9. The Nautical class is described in Figures 2, 6, 8, 10. Applied physics courses in the Engineering and Nautical classes have applied the method Problem Solving. The Teknika class is more detailed, detailed and neat in solving problems using problem solving methods, while the Nautika class looks standard (in general). After carrying out the analysis and discussion, it was concluded that the problem solving method in applied physics lectures for cadets of nautical engineering could be applied according to 4 stages of problem solving